Sovereign Default Risk and the U.S. Equity Market - Jeanneret, Alexandre (Journal of Financial and Quantitative Analysis, 2017)
This paper develops a two-country asset pricing model with defaultable firms and governments. This model shows that higher sovereign credit risk in a country depresses equity prices internationally and increases their volatility. The effect is strongest during adverse economic conditions and when firms are close to financial distress. A structural estimation provides evidence that sovereign default risk in Europe affects European and U.S. stock markets through the threat of an economic slowdown.